(untitled) (Itinera, 2016)
As a simple and ornamental object, the frame, turns into the principal vehicle of an extended philosophical reflexion: it becomes the setting and the connection – Georg Simmel used to define it as “bridge” and “door” - between Art world and Life world. In my work I start by examining the researches that Leon Battista Alberti completed on picture and works of art of his time; passing through the philosophical theories of Georg Simmel, José Ortega y Gasset and phenomenology of Eugen Fink, I have come to Victor Stoichita recent studies which deal with the past Dutch picture and Surrealism of the XX century. Through this path, the reflexion on the setting role and form into the art representation is the central idea that lasts until these days and opens new philosophical sceneries. This study enriches the contemporary debate and gives new meanings and prospects to art interpretation.